Is Children's Understanding of Nontraditional Advertising Comparable to Their Understanding of Television Advertising?. (September 2013) - Owen, Laura; Lewis, Charlie; Auty, Susan; Buijzen, Moniek
The dramatic changes in children's commercial environment call for an updated evaluation of children's grasp of advertising. The aim of this study is to compare children's understanding of television advertising with nontraditional advertising (i.e., movie and in-game brand placement, product licensing, program sponsorship, and advergames). The authors interviewed 134 children from second-grade (ages 6–7) and fifth-grade (ages 9–10) classes in the United Kingdom about the nature and intent of different examples of advertising, combining open-ended and cued response formats. As anticipated, children demonstrated a significantly more sophisticated understanding of television advertising compared with nontraditional advertising. Embedded advertising practices (movie and in-game brand placement) were most difficult for children to understand. Thus, children appear to have limited knowledge of alternative marketing tactics and consequently lack the cognitive skills to evaluate them critically. The authors conclude by making suggestions for public policy measures.